Spatial Hearing Questionnaire: Psychometric Properties of Turkish Version and Correlations with Hearing Skills - ÇILDIR, Bünyamin; TOKGÖZ-YILMAZ, Suna; SENNAROĞLU, Gonca (Archives of Acoustics, 2021)
Objective: Self-report questionnaire is informative to assess general hearing disability. The aims of this study were to investigate the reliability of Turkish version of spatial hearing questionnaire (SHQ) and to analyze the validity of the SHQ by the correlation with speech, spatial, and qualities of hearing questionnaire (SSQ) and Turkish matrix sentence test (TMST). Methods: The first part of the study was the psychometric properties of the SHQ with 192 participants (137 with normal hearing, 55 with hearing loss). In the second and main part of the study, we applied two questionnaires (SHQ and SSQ) and TMST to people other than those included in the first part of the study (88 participants with bilateral sensorineural hearing loss). We compared the results of these two questionnaires and the TMST with the speech discrimination (SD) scores. Results: Turkish spatial hearing questionnaire’s internal consistency was 0.94 and 0.97 for individuals with normal hearing and for individuals with hearing loss, respectively. Moderate, positive, statistically significant correlation was observed between the SHQ and SSQ (r = 0:606, p = 0:001 in individuals with hearing loss who do not wear any hearing aid, and r = 0:627, p = 0:001 in hearing aid users), and SHQ and SD (r = 0:561, p = 0:032 in hearing aid users). According to TMST, moderate, positive, statistically significant correlation was found between SSQ and adaptive TMST in individuals with hearing loss who do not wear any hearing aid (r = 0:330, p = 0:033 for S0N90 and r = 0:364, p = 0:018 for S0N270). Conclusions: Turkish SHQ is a valid and reliable questionnaire for assessing hearing functions. SHQ, SSQ, and TMST are clinically beneficial measuring tools in planning the process of hearing rehabilitation and follow-up.